ANALISIS PENGUASAAN “DIANR” DAN “XIE” PADA MAHASISWA UNIVERSITAS TANJUNGPURA PRODI MANDARIN ANGKATAN 2015 - Erni Permatasari; Ina Ina; Bun Yan Khiong (Universitas Tanjungpura, 2019)
AbstractBoth of “dianr” and “xie” are belonged to indefinite measure word which used to indicate the indefinite amount. Even “dianr” and “xie” are equally belonged to a same word class, but the differences between them are lie in what the words meant and how its used. “dianr” can be used to express an indefinite amount, as well as “xie” but the amount which expressed was different. The amount that expressed by “dianr” is less than “xie”. Therefore, students may encounter some obstacles whenever they learn and use them, for example, there were some students who assumed that “dianr” and “xie” were same and can be substituting each other. In order to understand the mastery condition and difficulties of “dianr” and “xie” of Tanjungpura University Chinese Major year 2015 students, researcher used Literature Study Method and Test Method. The research results represent that Tanjungpura University Chinese Major year 2015 students can master “dianr” and “xie” well, with their mastery percentage that reached 75.47% and 71.59%. Keywords: dianr, Mastery Condition, xie